PENGARUH LIKUIDITAS, SOLVABILITAS, AKTIVITAS, SUKU BUNGA, DAN TINGKAT INFLASI TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN DI SEKTOR ENERGI TAHUN 2022-2024 - Prihastono, Damar (Seminar Nasional Manajemen, 2026)
This study aims to determine the influence of liquidity, solvency, activity, interest rates, and inflation on financial performance in the energy sector in 2022-2024. Quantitative data from secondary sources were used as research data. The population studied was energy sector companies in 2022-2024. The sampling technique was purposive sampling. Data analysis was performed using multiple linear regression with the help of SPSS 25 software. This study found that liquidity, interest rates, and inflation had no effect on financial performance. Meanwhile, solvency had a significant negative effect on financial performance. Activity also had a positive effect on financial performance in the energy sector in 2022-2024. Therefore, companies should not rely solely on macroeconomic and liquidity factors, but should focus on strengthening operational efficiency, optimizing asset turnover, and selectively managing debt structures to improve financial performance. Keywords: Liquidity; Solvency; Activity; Macroeconomics; Profitability